Development of a Phage Cocktail to Prevent Catheter-Associated Urinary Tract Infections - Amorim, Catarina Domingues (2018)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2017